Emerging trends in animal ecology research (Zoological Records and Reviews, 2025)
Animal ecology has undergone a period of profound methodological and conceptual renewal over the past decade,driven by technological advances in biologging, remote sensing, molecular ecology, and computational modelling thathave fundamentally expanded the spatial, temporal, and biological scales at which ecological processes can be studied.This review synthesises emerging trends in animal ecology research from 224 primary studies published 2015-2025,identifying six major research frontiers: (i) movement ecology and the Animal Internet of Things (AioT), enabled byminiaturised GPS-GSM and satellite telemetry tags; (ii) functional trait-based ecology, replacing species-identity withtrait-mediated mechanistic models of ecosystem function; (iii) landscape genomics, integrating population genetics withspatial environmental data to identify adaptive variation and connectivity; (iv) animal microbiome ecology, examining howgut and skin microbiomes mediate host fitness, immunity, and ecological interactions; (v) community ecology undermultiple stressors, developing multi-stressor frameworks that replace single-factor experimental designs; and (vi)macroecological synthesis enabled by global biodiversity databases (GBIF, eBird, MoveBank) and machine learning. Abibliometric analysis of 14,820 animal ecology publications (2015-2024) reveals the fastest-growing subfields andidentifies Europe's comparative research strengths and gaps. Cross-cutting themes -- open data practices,reproducibility, and the integration of Indigenous and local ecological knowledge -- are assessed for their transformativepotential. A forward-looking agenda prioritises five research directions for the 2025-2035 decade in European animalecology.